Artículo. Concepciones y prácticas evaluativas docentes: una mirada a dos instituciones del Municipio de Magangué, Bolívar (2018)
The learning evaluation process is structured as a fundamental tool to improve the teaching and learning processes, primarily if it is developed from a formative perspective, such as what is proposed in the new trends on evaluation of learning and Decree 1290 of April 16 of 2009. Under this perspective, the present research project, Conceptions and evaluative teaching practices: a look at two institutions in the Municipality of Magangué, sought to analyze the existing relationship from the understanding of Decree 1290/09, with the purpose of unveiling better the phenomenon studied, thus generating a reflection from the same pedagogical exercise, so that the results thrown up during the evaluationprocess of learning are not understood as quantitative figures of the teaching-learning process. For this reason, the methodological design, which underpins the research is the interpretive hermeneutical paradigm. In correspondence with this paradigm, research was based on the qualitative approach, since intentionality is "to interpret the phenomenon according to the meanings it has for the people involved" (Rodríguez, Gil & García 1996. P.32). Consequently, the method used in tune with the qualitative approach was the dialectic hermeneutic, as it potentializes the best possible interpretation of writings, words and human behavior, generating an approach with the research subject. Which was developed with the participation of twenty three teachers, with whom a self-administered questionnaire, a focus group and the observation of two classes were applied...